Compound, preparation method of compound, resin material and application of resin material
By using compounds containing sulfide ether, aromatic groups and thioamide structural units to prepare resin materials, the problem of low refractive index of existing optical resin materials is solved, and high refractive index, good light transmittance and various advantages are achieved. Performance, suitable for efficient optical applications.
Patent Information
- Application Number
- CN202411448746.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-02-18
AI Technical Summary
The existing optical resin materials have a low refractive index and are difficult to meet the needs of efficient optical applications.
A resin material is prepared by polymerization by using a compound containing sulfide ether, aromatic groups and thioamide structural unit to improve its refractive index and light transmittance.
It has achieved a high refractive index (can reach more than 1.8), good light transmittance, mechanical properties, heat resistance and low water absorption, and is suitable for AR glasses display and other fields.
Smart Images

Figure CN119463087A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of optical materials, and in particular to a compound and a preparation method thereof, a resin material and an application thereof. Background Art
[0002] Optical materials are mainly divided into two categories: glass and resin, and are widely used in many fields such as display, lens, sensor, etc. Among them, optical resin materials are gaining more and more attention in the field of optical materials. Refractive index is one of the most important indicators reflecting optical resin materials.
[0003] Therefore, how to improve the refractive index of optical resin materials has become an urgent problem to be solved. Summary of the invention
[0004] In view of this, the present application proposes a compound and a preparation method thereof, a resin material and an application thereof.
[0005] The first aspect of the present application provides a compound having the following general formula:
[0006]
[0007] Wherein, R1, R2 and R3 are all aromatic groups;
[0008] m is a positive integer, 1≤m≤10000.
[0009] In some embodiments, R1, R2 and R3 are each selected from one of a benzene ring, a naphthalene ring, fluorene, carbazole, furan, thiophene, pyrrole, thiazole, imidazole, pyridine, pyrazine, pyrimidine and pyridazine.
[0010] In some embodiments, the compound has the following structural formula:
[0011] or,
[0012] or,
[0013] or,
[0014] or,
[0015]
[0016] A second aspect of the present application provides a resin material comprising the above-mentioned compound.
[0017] A third aspect of the present application provides an application of a resin material in optical waveguide technology.
[0018] The fourth aspect of the present application provides a method for preparing a compound, the preparation method comprising:
[0019] Providing sulfur, a first monomer, and a second monomer;
[0020] Mixing the sulfur element, the first monomer and the second monomer and performing a polymerization reaction to obtain the compound;
[0021] Wherein, the general formula of the first monomer is as follows:
[0022]
[0023] The general formula of the second monomer is as follows:
[0024]
[0025] Wherein, Ar in the general formula of the first monomer and the second monomer are both aromatic groups.
[0026] In some embodiments, Ar is a benzene ring or a triazine.
[0027] In some embodiments, the first monomer is selected from at least one of 4,4'-diaminodiphenyl sulfide, 6,6'-thioether-bis(2-aminopyridine), 4,4'-thioether-bis(1,3,5-triazine-2-amine), and 4,4'-(1,4-phenylene di(thio)) diphenylamine.
[0028] In some embodiments, the second monomer is selected from at least one of pyridine-3,5-dicarboxaldehyde, 1H-pyrrole-2,5-dicarboxaldehyde, and 2,5-thiophene dicarboxaldehyde.
[0029] In some embodiments, the mixing and polymerization of the sulfur element, the first monomer, and the second monomer to obtain the compound includes: mixing and polymerization of the sulfur element, the first monomer, the second monomer, a catalyst, and a solvent to obtain the compound.
[0030] In some embodiments, the catalyst is selected from at least one of potassium hydroxide, sodium hydroxide, sodium carbonate, and potassium carbonate.
[0031] In some embodiments, the solvent is selected from at least one of pyridine, aliphatic amines, alcohol amines, amides, alicyclic amines, aromatic amines, and naphthyl amines.
[0032] In some embodiments, the step of mixing the sulfur element, the first monomer, and the second monomer and performing a polymerization reaction to obtain the compound comprises:
[0033] Inert gas is introduced into a reaction container, and sulfur, a first monomer, a second monomer and a catalyst are added respectively;
[0034] Then injecting a solvent to dissolve the components in the reaction vessel to form a solution;
[0035] The solution is heated and stirred continuously to promote the reaction;
[0036] The reacted solution is filtered and then precipitated to form a precipitate;
[0037] The precipitate is washed and then dried under vacuum to form the compound.
[0038] In some embodiments, the solution is heated to 100°C-120°C and stirred for 5 hours-10 hours to promote the reaction; and / or, the solution after the reaction is filtered and added into methanol or ethanol for precipitation to form a precipitate, and the precipitate is filtered and washed with methanol or ethanol, and then vacuum dried at 40°C-50°C to form the compound.
[0039] As can be seen from the above-mentioned technical scheme, the compound proposed in the present application, mainly comprising three structural units of thioether, aromatic group and thioamide, has higher refractive index, good light transmittance and good mechanical properties, heat resistance and low water absorption. Moreover, the hydrogen bond acceptor and donor of the compound of the present application embodiment are present in the main chain structure of the resin, and the introduction process does not require additional modification steps, thereby simplifying the synthesis process, reducing process difficulty and production cost. Moreover, by directly embedding hydrogen bond acceptor and donor into the main chain, its solubility can be optimized, the molecular weight of the resin is improved, and its thermal stability and processing properties are improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained like these drawings without paying any creative work.
[0041] Figure 1 It is the general structural formula of the compound proposed in this application.
[0042] Figure 2 It is a schematic diagram of the reaction principle for preparing the P1 compound proposed in this application.
[0043] Figure 3 It is a schematic diagram of the reaction principle for preparing P2 compound proposed in this application.
[0044] Figure 4It is a schematic diagram of the reaction principle for preparing the P3 compound proposed in this application.
[0045] Figure 5 It is a schematic diagram of the reaction principle for preparing the P4 compound proposed in this application.
[0046] Figure 6 It is a schematic diagram of the reaction principle for preparing the P5 compound proposed in this application.
[0047] Figure 7 It is a schematic diagram of the process for preparing the compound proposed in this application. DETAILED DESCRIPTION
[0048] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0049] It should also be understood that the terms used in this application specification are only for the purpose of describing specific embodiments and are not intended to limit the application. As used in this application specification and the appended claims, unless the context clearly indicates otherwise, the singular forms "a", "an" and "the" are intended to include plural forms.
[0050] It should be further understood that the term “and / or” used in the specification and appended claims refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations.
[0051] Optical materials are mainly divided into two categories: glass and resin, and are widely used in many fields such as display, lens, sensor, etc. For example, they are used in the field of AR glasses display. Among them, optical resin materials are gaining more and more attention in the field of optical materials due to their advantages such as low specific gravity, high impact toughness, rich structural design, and easy processing. The refractive index is one of the most important indicators reflecting optical resin materials. A higher refractive index can effectively improve light efficiency, reduce lens thickness, reduce costs, and obtain a good wearing experience.
[0052] Therefore, how to improve the refractive index of optical resin materials has become an urgent problem to be solved. In the prior art, by introducing hydroxyl groups into the benzene ring of polyphenylene sulfide, on the one hand, the structure of polyphenylene sulfide can be transformed from a crystalline polymer to an amorphous polymer to improve light transmittance, and on the other hand, hydrogen bonding cross-linking effect can occur between the introduced hydroxyl groups to increase the resin density and thus the refractive index. However, the synthesis process of hydroxyl-modified polyphenylene sulfide is complicated, the benzene ring is easily yellowed due to oxidation, the solubility is poor, and the molecular weight is low and difficult to process, so there are still many difficulties to overcome before practical application.
[0053] Thus, the present application embodiment provides a compound, mainly comprising three structural units of thioether, aromatic group and thioamide, with high refractive index, good light transmittance and good mechanical properties, heat resistance and low water absorption. Not only that, the hydrogen bond acceptor and donor of the compound of the present application embodiment are both present in the main chain structure of the resin, and the introduction process does not require additional modification steps, thereby simplifying the synthesis process, reducing the process difficulty and production cost. Moreover, by directly embedding the hydrogen bond acceptor and donor into the main chain, its solubility can be optimized, the molecular weight of the resin can be improved, and its thermal stability and processing properties can be improved. In addition, in traditional hydroxy-modified polyphenylene sulfide, the hydroxyl group on the benzene ring may become the active site of the oxidation reaction, causing the resin to be easily oxidized in the presence of light, high temperature or oxygen, thereby causing yellowing. And directly embedding the hydrogen bond acceptor and donor into the main chain can reduce or eliminate these active sites, improve the oxidation resistance and stability of the resin, and prevent the occurrence of yellowing. In summary, the compound of the present application can avoid the various problems of hydroxy-modified polyphenylene sulfide.
[0054] The compounds provided in the examples of the present application have the following general formula:
[0055]
[0056] Wherein, R1, R2 and R3 are all aromatic groups; m is a positive integer, 1≤m≤10000.
[0057] Exemplarily, m can be 1, 10, 100, 200, 300, 400, 500, 600, 700, 800, 900, 1000, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000, 10000, etc., any value between 1 and 10000.
[0058] The compounds of the embodiments of the present application mainly include three structural units: thioether, aromatic group and thioamide, and have a high refractive index. On the one hand, they benefit from the high unsaturation in the structure. For example, thioamide and aromatic group have a high proportion of sulfur atoms, so they have high unsaturation. The unsaturated bonds and ring structures in the molecules will enhance the electronic polarization ability of the molecules, thereby increasing the refractive index; on the other hand, they benefit from abundant hydrogen bond acceptors, such as nitrogen atoms in thiocarbonyl, thioether, thioamide and nitrogen atoms with lone pairs of electrons in aromatic rings, which can be used as hydrogen bond acceptors. The presence of hydrogen bond acceptors can increase the interaction force between molecules, which will change the behavior of molecules in the light field, thereby affecting the refractive index. Specifically, the formation of hydrogen bonds can make the electron clouds between molecules more closely arranged, increase the electronic polarizability, and thus increase the refractive index. Rich hydrogen bond donors include NH bonds in thioamide and aromatic rings. Multiple and unequal hydrogen bond effects can enhance the interaction force between resin molecules and achieve a densely packed effect, thereby further increasing the refractive index to more than 1.8.
[0059] The compounds of the embodiments of the present application also have good light transmittance. On the one hand, due to the large atomic radius of the sulfur atom, the distance between groups / atoms or groups / groups is far, making it difficult to form a conjugated structure, and the light absorption is weaker. On the other hand, the rich variety and varying strength of hydrogen bonds in the resin can effectively avoid the formation of an ordered crystalline structure between resin molecules, and instead form an amorphous stacking structure, which can effectively avoid light scattering and enhance light transmittance.
[0060] The compounds of the examples of the present application also have good mechanical properties, heat resistance and low water absorption. The rigid structure of the aromatic group and the low chain freedom of the polymer molecules have a great contribution to the mechanical properties, heat resistance and low water absorption of the resin.
[0061] In an optional embodiment, R1, R2 and R3 are respectively selected from one of a benzene ring, a naphthalene ring, fluorene, carbazole, furan, thiophene, pyrrole, thiazole, imidazole, pyridine, pyrazine, pyrimidine and pyridazine. R1, R2 and R3 may be the same aromatic group or different aromatic groups.
[0062] In an alternative embodiment, the compound may include a P1 compound (eg Figure 2 As shown), P2 compound (such as Figure 3 As shown), P3 compound (as Figure 4 ), P4 compound (as shown in 5) and P5 compound (as shown in Figure 6 Of course, in other embodiments, the compound may also be of other structures, mainly comprising three structural units of thioether, aromatic group and thioamide, within the scope of the above general formula.
[0063] As an embodiment, the structural formula of the P1 compound may be:
[0064]
[0065] Among them, the refractive index of the P1 compound is 1.808, which has a high refractive index. In the field of AR glasses display, the P1 compound as a resin material has a high refractive index, which can effectively improve the light efficiency, reduce the thickness of the lens, reduce the cost and obtain a good wearing experience.
[0066] As an embodiment, the structural formula of the P2 compound may be:
[0067]
[0068] Among them, the refractive index of the P2 compound is 1.814, which has a high refractive index. In the field of AR glasses display, the P2 compound as a resin material has a high refractive index, which can effectively improve the light efficiency, reduce the thickness of the lens, reduce the cost and obtain a good wearing experience.
[0069] As an embodiment, the structural formula of the P3 compound may be:
[0070]
[0071] Among them, the refractive index of the P3 compound is 1.811, which has a high refractive index. In the field of AR glasses display, the P3 compound as a resin material has a high refractive index, which can effectively improve the light efficiency, reduce the thickness of the lens, reduce the cost and obtain a good wearing experience.
[0072] As an embodiment, the structural formula of the P4 compound may be:
[0073]
[0074] Among them, the refractive index of the P4 compound is 1.826, which has a high refractive index. In the field of AR glasses display, the P4 compound as a resin material has a high refractive index, which can effectively improve the light efficiency, reduce the thickness of the lens, reduce the cost and obtain a good wearing experience.
[0075] As an embodiment, the structural formula of the P5 compound may be:
[0076]
[0077] Among them, the refractive index of the P5 compound is 1.819, which has a high refractive index. In the field of AR glasses display, the P5 compound as a resin material has a high refractive index, which can effectively improve the light efficiency, reduce the thickness of the lens, reduce the cost and obtain a good wearing experience.
[0078] The present application also provides a resin material including the above-mentioned compound. Since the resin material includes the above-mentioned compound, the resin material provided in the present application has the properties and beneficial effects of the above-mentioned compound, which will not be described one by one here.
[0079] The embodiment of the present application also provides an application of resin materials in optical waveguide technology. For example, in the field of AR glasses display, the optical waveguide technology based on the diffraction principle uses resin materials as a substrate, and realizes the coupling, total reflection propagation and coupling out of light through a grating with a specific structure, thereby transmitting the light signal emitted by the image source to the human eye to form a virtual image. In the field of AR glasses display, the resin material has a higher refractive index, which can effectively improve the light efficiency, reduce the thickness of the lens, reduce the cost and obtain a good wearing experience.
[0080] The present application also provides a method for preparing a compound, the method comprising:
[0081] S1, providing sulfur, a first monomer and a second monomer;
[0082] S2, mixing the sulfur element, the first monomer and the second monomer and performing a polymerization reaction to obtain the compound;
[0083] Wherein, the general formula of the first monomer is as follows:
[0084]
[0085] The general formula of the second monomer is as follows:
[0086]
[0087] Wherein, Ar in the general formula of the first monomer and the second monomer are both aromatic groups.
[0088] The preparation method of the compound proposed in the examples of the present application has simple steps and does not require additional modification steps during the introduction process, thereby simplifying the synthesis process and reducing the process difficulty and production cost.
[0089] In an alternative embodiment, Ar is a benzene ring or a triazine.
[0090] In an optional embodiment, the first monomer is selected from at least one of 4,4'-diaminodiphenyl sulfide, 6,6'-thioether-bis(2-aminopyridine), 4,4'-thioether-bis(1,3,5-triazine-2-amine), and 4,4'-(1,4-phenylene di(thio)) diphenylamine.
[0091] In an optional embodiment, the second monomer is selected from at least one of pyridine-3,5-dicarboxaldehyde, 1H-pyrrole-2,5-dicarboxaldehyde and 2,5-thiophene dicarboxaldehyde.
[0092] In an optional embodiment, the step of mixing the sulfur element, the first monomer and the second monomer and subjecting them to a polymerization reaction to obtain the compound includes: mixing the sulfur element, the first monomer, the second monomer, a catalyst and a solvent and subjecting them to a polymerization reaction to obtain the compound.
[0093] In an optional embodiment, the catalyst is selected from at least one of potassium hydroxide, sodium hydroxide, sodium carbonate and potassium carbonate.
[0094] In an optional embodiment, the solvent is selected from at least one of pyridine, aliphatic amines, alcohol amines, amides, alicyclic amines, aromatic amines, and naphthyl amines.
[0095] In an optional embodiment, the step of mixing the sulfur element, the first monomer, and the second monomer and performing a polymerization reaction to obtain the compound comprises:
[0096] Inert gas is introduced into a reaction container, and sulfur, a first monomer, a second monomer and a catalyst are added respectively;
[0097] Then injecting a solvent to dissolve the components in the reaction vessel to form a solution;
[0098] The solution is heated and stirred continuously to promote the reaction;
[0099] The reacted solution is filtered and then precipitated to form a precipitate;
[0100] The precipitate is washed and then dried under vacuum to form the compound.
[0101] As an implementation method, the first monomer can be 4,4'-diaminodiphenyl sulfide, the second monomer can be pyridine-3,5-dicarboxaldehyde, the catalyst can be potassium hydroxide, and the solvent can be pyridine. Specifically, the weights of the above components are as follows: sulfur element 72 mg; 4,4'-diaminodiphenyl sulfide 108.2 mg; pyridine-3,5-dicarboxaldehyde 135.1 mg; potassium hydroxide 56.1 mg; pyridine 0.63 mL.
[0102] As an embodiment, the first monomer can be 6,6'-sulfide-bis(2-aminopyridine), the second monomer can be 1H-pyrrole-2,5-dicarboxaldehyde, the catalyst can be potassium hydroxide, and the solvent can be pyridine. Specifically, the weights of the above components are as follows: sulfur element 72 mg; 6,6'-sulfide-bis(2-aminopyridine) 109.1 mg; 1H-pyrrole-2,5-dicarboxaldehyde 123.1 mg; potassium hydroxide 56.1 mg; pyridine 0.63 mL.
[0103] As an embodiment, the first monomer can be 4,4'-sulfide-bis(1,3,5-triazine-2-amine), the second monomer can be 1H-pyrrole-2,5-dicarboxaldehyde, the catalyst can be potassium hydroxide, and the solvent can be pyridine. Specifically, the weights of the above components are as follows: sulfur element 72 mg; 4,4'-sulfide-bis(1,3,5-triazine-2-amine) 111.1 mg; 1H-pyrrole-2,5-dicarboxaldehyde 123.1 mg; potassium hydroxide 56.1 mg; pyridine 0.63 mL.
[0104] As an implementation method, the first monomer can be 4,4'-diaminodiphenyl sulfide, the second monomer can be 2,5-thiophene dicarboxaldehyde, the catalyst can be potassium hydroxide, and the solvent can be pyridine. Specifically, the weights of the above components are as follows: sulfur element 72 mg; 4,4'-diaminodiphenyl sulfide 108.2 mg; 2,5-thiophene dicarboxaldehyde 140.1 mg; potassium hydroxide 56.1 mg; pyridine 0.63 mL.
[0105] As an embodiment, the first monomer can be 4,4'-(1,4-phenylene di(sulfide)) diphenylamine, the second monomer can be pyridine-3,5-dicarboxaldehyde, the catalyst can be potassium hydroxide, and the solvent can be pyridine. Specifically, the weights of the above components are as follows: sulfur element 72 mg; 4,4'-(1,4-phenylene di(sulfide)) diphenylamine 162.3 mg; pyridine-3,5-dicarboxaldehyde 135.1 mg; potassium hydroxide 56.1 mg; pyridine 0.63 mL.
[0106] In some embodiments, the solution is heated to 100° C.-120° C. and stirred for 5 to 10 hours to promote the reaction. For example, in step S4, the solution may be heated to 100° C., 110° C., or 120° C., etc., and stirred for 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, or 10 hours, etc. to promote the reaction.
[0107] In some embodiments, the solution after the reaction is filtered and then added to methanol or ethanol for precipitation to form a precipitate, the precipitate is filtered and then washed with methanol or ethanol, and then vacuum dried at 40° C.-50° C. to form the compound. That is, the cleaning agent can be a solution such as methanol or ethanol, and can be vacuum dried at a temperature of 40° C. or 50° C. to form the compound.
[0108] As an implementation method, Figure 2 As shown, the P1 compound can be generated by the reaction of sulfur, 4,4'-diaminodiphenyl sulfide and pyridine-3,5-dicarboxaldehyde. The structure of the generated P1 compound is as follows:
[0109]
[0110] As an implementation method, Figure 3 As shown, the P2 compound can be generated by the reaction of sulfur, 6,6'-thioether-bis(2-aminopyridine) and 1H-pyrrole-2,5-dicarboxaldehyde. The structure of the generated P2 compound is as follows:
[0111]
[0112] As an implementation method, Figure 4 As shown, the P3 compound can be generated by the reaction of sulfur, 4,4'-thioether-bis(1,3,5-triazine-2-amine) and 1H-pyrrole-2,5-dicarboxaldehyde. The structure of the generated P3 compound is as follows:
[0113]
[0114] As an implementation method, Figure 5 As shown, the P4 compound can be generated by the reaction of sulfur, 4,4'-diaminodiphenyl sulfide and 2,5-thiophene dicarboxaldehyde. The structure of the generated P4 compound is as follows:
[0115]
[0116] As an implementation method, Figure 6 As shown, the P5 compound can be generated by the reaction of sulfur, 4,4'-(1,4-phenylenedi(sulfur))diphenylamine and pyridine-3,5-dicarboxaldehyde. The structure of the generated P5 compound is as follows:
[0117]
[0118] The compounds of the present invention are further described below in conjunction with specific examples and test data.
[0119] Example 1
[0120] Synthesis of P1 compound:
[0121] like Figure 1 As shown, in a nitrogen atmosphere, sulfur (72.0 mg, 2.25 mmol), 4,4'-diaminodiphenyl sulfide (108.2 mg, 0.5 mmol), pyridine-3,5-dicarboxaldehyde (135.1 mg, 1.0 mmol) and potassium hydroxide (56.1 mg, 1.0 mmol) were added to a 10 mL reaction bottle equipped with a magnetic stirring bar. Pyridine (0.63 mL) was then injected with a syringe to dissolve the monomer. The solution was heated to 110 ° C and stirred for 8 hours. The reacted solution was filtered to remove the solid insoluble matter, and the filtrate was added dropwise to 100 mL of methanol for precipitation. The precipitate was filtered and washed three times with methanol, and then vacuum dried at 40 ° C to form the P1 compound.
[0122] Example 2
[0123] Synthesis of P2 compound:
[0124] like Figure 2 As shown, under a nitrogen atmosphere, sulfur (72.0 mg, 2.25 mmol), 6,6'-thioether-bis(2-aminopyridine) (109.1 mg, 0.5 mmol), 1H-pyrrole-2,5-dicarboxaldehyde (123.1 mg, 1.0 mmol) and potassium hydroxide (56.1 mg, 1.0 mmol) were added to a 10 mL reaction bottle equipped with a magnetic stirring bar. Pyridine (0.63 mL) was then injected with a syringe to dissolve the monomer. The solution was heated to 110 ° C and stirred for 8 hours. The reacted solution was filtered to remove the solid insoluble matter, and the filtrate was added dropwise to 100 mL of methanol for precipitation. The precipitate was filtered and washed three times with methanol, and then vacuum dried at 40 ° C to form the P2 compound.
[0125] Example 3
[0126] Synthesis of P3 compounds:
[0127] like Figure 3As shown, in a nitrogen atmosphere, sulfur (72.0 mg, 2.25 mmol), 4,4'-thioether-bis(1,3,5-triazine-2-amine) (111.1 mg, 0.5 mmol), 1H-pyrrole-2,5-dicarboxaldehyde (123.1 mg, 1.0 mmol) and potassium hydroxide (56.1 mg, 1.0 mmol) were added to a 10 mL reaction bottle equipped with a magnetic stirring bar. Pyridine (0.63 mL) was then injected with a syringe to dissolve the monomer. The solution was heated to 110 ° C and stirred for 8 hours. The reacted solution was filtered to remove the solid insoluble matter, and the filtrate was added dropwise to 100 mL of methanol for precipitation. The precipitate was filtered and washed three times with methanol, and then vacuum dried at 40 ° C to form the P3 compound.
[0128] Example 4
[0129] Synthesis of P4 compounds:
[0130] like Figure 4 As shown, under a nitrogen atmosphere, sulfur (72.0 mg, 2.25 mmol), 4,4'-diaminodiphenyl sulfide (108.2 mg, 0.5 mmol), 2,5-thiophene dicarboxaldehyde (140.1 mg, 1.0 mmol) and potassium hydroxide (56.1 mg, 1.0 mmol) were added to a 10 mL reaction bottle equipped with a magnetic stirring bar. Pyridine (0.63 mL) was then injected with a syringe to dissolve the monomer. The solution was heated to 110 ° C and stirred for 8 hours. The reacted solution was filtered to remove the solid insoluble matter, and the filtrate was added dropwise to 100 mL of methanol for precipitation. The precipitate was filtered and washed three times with methanol, and then vacuum dried at 40 ° C to form the P4 compound.
[0131] Example 5
[0132] Synthesis of P5 compound:
[0133] like Figure 5 As shown, in a nitrogen atmosphere, sulfur (72.0 mg, 2.25 mmol), 4,4'-(1,4-phenylene di(sulfide)) diphenylamine (162.3 mg, 0.5 mmol), pyridine-3,5-dicarboxaldehyde (135.1 mg, 1.0 mmol) and potassium hydroxide (56.1 mg, 1.0 mmol) were added to a 10 mL reaction bottle equipped with a magnetic stirring bar. Pyridine (0.63 mL) was then injected with a syringe to dissolve the monomer. The solution was heated to 110 ° C and stirred for 8 hours. The reacted solution was filtered to remove the solid insoluble matter, and the filtrate was added dropwise to 100 mL of methanol for precipitation. The precipitate was filtered and washed three times with methanol, and then vacuum dried at 40 ° C to form the P5 compound.
[0134] The compounds prepared in Examples 1 to 5 above were subjected to the following tests.
[0135] 1. Refractive index test. The purified resin is dispersed in a polar solvent, such as tetrachloroethane, and then spin-coated on a silicon wafer by spin coating. After baking, the refractive index is tested using an ellipsometer. The refractive indexes of the compounds prepared in Examples 1 to 5 are shown in Table 1.
[0136] 2. Abbe number test. The Abbe number is calculated by the refractive index at wavelengths of 486.nm, 587.6nm and 656.3nm. The calculation formula is as follows:
[0137] Vd=(n D -1) / (n F -n C )
[0138] The Abbe numbers of the compounds prepared in Examples 1 to 5 obtained through testing are shown in Table 1.
[0139] 3. Water absorption test. The compound prepared in each example was injected into a plate-shaped molded piece with a thickness of 2 mm, and the water absorption after immersion at 23°C for 24 hours was measured according to ISO62. The water absorption of the compounds prepared in Examples 1 to 5 was shown in Table 1.
[0140] 4. Transmittance test. The purified resin is dispersed in a polar solvent, such as tetrachloroethane, and then spin-coated on the surface of a glass substrate by spin coating. After baking, the test is performed using a haze meter. The transmittances of the compounds prepared in Examples 1 to 5 are shown in Table 1.
[0141] 5. Glass transition temperature (Tg) test. The test was performed using a 2910 differential scanning calorimeter manufactured by TA Instruments Japan at a heating rate of 10°C / min. The glass transition temperatures (Tg) of the compounds prepared in Examples 1 to 5 are shown in Table 1.
[0142] The experimental comparison data and analysis are as follows:
[0143] Table 1
[0144] Refractive Index Abbe number Water absorption (%) Light transmittance (%) Tg Example 1 1.808 31 0.11% 87% 152℃ Example 2 1.814 27 0.12% 85% 154℃ Example 3 1.811 29 0.12% 85% 153℃ Example 4 1.826 22 0.08% 83% 156℃ Example 5 1.819 24 0.1% 83% 156℃
[0145] As shown in the table above: the compounds prepared in Examples 1 to 5 all have a high refractive index, good light transmittance, good mechanical properties, heat resistance and low water absorption. Therefore, the compounds in the examples of the present application all have a high refractive index, good light transmittance, good mechanical properties, heat resistance and low water absorption.
[0146] Those skilled in the art may combine and associate different embodiments or examples described in this specification as well as features of different embodiments or examples without mutual contradiction.
[0147] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed in the present application, and these modifications or replacements should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.
Claims
1. A compound, characterized in that The compound has the following general formula: Wherein, R1, R2 and R3 are all aromatic groups; m is a positive integer, 1≤m≤10000.
2. The compound according to claim 1, characterized in that R1, R2 and R3 are each selected from one of a benzene ring, a naphthalene ring, fluorene, carbazole, furan, thiophene, pyrrole, thiazole, imidazole, pyridine, pyrazine, pyrimidine and pyridazine.
3. The compound according to claim 1, characterized in that The structural formula of the compound is as follows:
4. A resin material, characterized in that: The resin material comprises the compound according to any one of claims 1 to 3.
5. Use of the resin material according to claim 4 in optical waveguide technology.
6. A method for preparing the compound according to any one of claims 1 to 3, characterized in that: The preparation method comprises: Providing sulfur, a first monomer, and a second monomer; Mixing the sulfur element, the first monomer and the second monomer and performing a polymerization reaction to obtain the compound; Wherein, the general formula of the first monomer is as follows: The general formula of the second monomer is as follows: Wherein, Ar in the general formula of the first monomer and the second monomer are both aromatic groups.
7. The preparation method according to claim 6, characterized in that: Ar is a benzene ring or a triazine.
8. The preparation method according to claim 6, characterized in that: The first monomer is at least one selected from 4,4'-diaminodiphenyl sulfide, 6,6'-sulfide-bis(2-aminopyridine), 4,4'-sulfide-bis(1,3,5-triazine-2-amine) and 4,4'-(1,4-phenylene di(sulfide)) diphenylamine.
9. The preparation method according to claim 6, characterized in that: The second monomer is selected from at least one of pyridine-3,5-dicarboxaldehyde, 1H-pyrrole-2,5-dicarboxaldehyde and 2,5-thiophene dicarboxaldehyde.
10. The preparation method according to claim 6, characterized in that: The step of mixing the sulfur element, the first monomer and the second monomer and performing a polymerization reaction to obtain the compound comprises: The sulfur element, the first monomer, the second monomer, a catalyst and a solvent are mixed and subjected to a polymerization reaction to obtain the compound.
11. The preparation method according to claim 10, characterized in that: The catalyst is selected from at least one of potassium hydroxide, sodium hydroxide, sodium carbonate and potassium carbonate.
12. The preparation method according to claim 10, characterized in that: The solvent is selected from at least one of pyridine, aliphatic amines, alcohol amines, amides, alicyclic amines, aromatic amines, and naphthyl amines.
13. The preparation method according to claim 10, characterized in that: The step of mixing the sulfur element, the first monomer and the second monomer and performing a polymerization reaction to obtain the compound comprises: Inert gas is introduced into a reaction container, and sulfur, a first monomer, a second monomer and a catalyst are added respectively; Then injecting a solvent to dissolve the components in the reaction vessel to form a solution; The solution is heated and stirred continuously to promote the reaction; The reacted solution is filtered and then precipitated to form a precipitate; The precipitate is washed and then dried under vacuum to form the compound.
14. The preparation method according to claim 13, characterized in that: The solution is heated to 100°C-120°C and stirred for 5 hours-10 hours to promote the reaction; and / or, The solution after the reaction is filtered and then added into methanol or ethanol for precipitation to form a precipitate. The precipitate is filtered and then washed with methanol or ethanol, and then vacuum dried at 40° C.-50° C. to form the compound.